Factors influencing the price of value-added calves at Superior Livestock Auction - Zimmerman, Lance C. (Kansas State University, 2010)
Value-added management at the cow-calf level is integrated across breeding, health and nutrition programs. Hedonic pricing models are necessary to navigate through the layered management standards imposed by certified health and marketing programs on the cow-calf sector. Previous research in feeder calf pricing models provides insight on the use and development of ordinary least squares in estimating price effects. Breed, vaccination program, age-and-source verification and natural-beef production have become more relevant as vertical coordination has influenced commercial cow-calf producers. This study provides the industry with new information pertaining to the revenue opportunities that exist for cow-calf producers through increased coordination in the beef industry. Video and satellite auction markets are recognized as a national pricing mechanism for feeder cattle in the United States. These markets represent the management and marketing practices of national cow-calf producers and the tastes and preferences of a national stocker and feedlot industry. Previous research in feeder cattle pricing models is applied to the current genetic, management, marketing and market structure information from video auction markets to discover relevant price effects pertaining to value-added calf production. More intensive value-added management practices were expected to enhance the revenue of cow-calf producers selling their calves through video auction markets. This research confirms that verified health and genetic claims produce higher calf prices compared to commodity calves. Weaned calves with at least two rounds of respiratory vaccinations generated an additional $5.50 to $7.50 per cwt., and weaning created $2.75 to $4.50 per cwt. in premiums over non-certified health programs. There were statistical differences among the premiums for each aggregated breed influence, and Angus and black and black-white faced cattle offered the highest breed premiums at $5.25 to $7.50 per cwt. compared to Brahman-influenced calves. Age-and-source verification presents the best opportunity for video auction market premiums among recently developed marketing programs. Statistically significant premiums ranged from $1.25 to $2.00 per cwt. for both steers and heifers over the last five years.
Keywords: Hedonic pricing model; Feeder calves; Feeder cattle; Value-added management; Superior Livestock Auction; Video auction market; Agriculture, General (0473); Economics, Agricultural (0503)